The levels of women's awareness, experience, acceptability and preference for Vaginal Human Papillomavirus (HPV) self-sampling in three provinces of China: a cross-sectional study - Jia Song; Yi-Hua Ni; Jing Fang; Shui-Xiang Qu; Xiao-Yan Chen; Wei-Li Wu; Wei-Chu Zhang; Jian-Fen Qin (BMC, 2024)
Abstract Background The primary screening technique for precancerous lesions and cervical cancer is human papillomavirus (HPV) testing, and HPV self-sampling has been shown to be consistent with clinician sampling in terms of the accuracy of the results and may improve cervical cancer screening rates. The aim of this study was to understand the level of awareness, experience, acceptability, and preference for vaginal HPV self-sampling among women in Jiangsu, Zhejiang, and Shanghai, China, and to analyze the possible influencing factors to determine the feasibility of implementing self-sampling. Methods Overall, 1793 women were included in the data analysis. A self-administered questionnaire was utilized. In addition to descriptive analysis, univariate and multivariate analyses were used to explore the associations between sociodemographic features, history of cervical cancer screening, and the level of awareness, experience, acceptability, and preference for HPV self-samples. Results The participants' level of awareness of and experience with HPV self-sampling were moderate. A total of 88.8% of participants rated the acceptability as "high", and self-sampling was preferred by 64.2% of them for cervical cancer screening. People aged 45 to 54 years showed a preference for both clinician sampling(OR = 1.762 (1.116-2.163)) and self-sampling (OR = 1.823 (1.233-2.697)). Those who had graduated from high school or above (OR = 2.305 (1.517-3.503), OR = 2.432 (1.570-3.768), OR = 3.258 (2.024-5.244)) preferred clinician-sampling, and those with a bachelor's degree or above (OR = 1.664 (1.042-2.657)) preferred self-sampling. Middle- and high-income individuals showed no preference for either sampling method (OR < 1). Conclusions HPV self-sampling is widely accepted, but awareness, experience and preferences need to be improved. These results may help to adjust public health strategies for the early inclusion of HPV self-sampling as a screening method in national initiatives to prevent cervical cancer.